Media Framing of the ‘Barking Student’ Case in the National News of Kompas.com and Tempo.co: Framing Media atas Kasus 'Siswa Menggonggong' dalam Portal Berita Nasional Kompas.com dan Tempo.co - Zaskia Firyal Rachman; Hanna Nurhaqiqi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the digital age, online media significantly shape public perception, particularly on social issues like bullying. Specific Background: The case of a high school student coerced into barking by a parent drew national attention, highlighting divergent media narratives. Knowledge Gap: Despite growing media coverage of bullying, limited research has examined how different news platforms frame the same incident. Aims: This study investigates how Kompas.com and Tempo.co framed the